2020
DOI: 10.2196/preprints.19434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Telehealth Home Support During COVID-19 Confinement for Community-Dwelling Older Adults With Mild Cognitive Impairment or Mild Dementia: Survey Study (Preprint)

Abstract: BACKGROUND The public health emergency of coronavirus disease (COVID-19) is rapidly evolving worldwide; some countries, including Spain, have implemented restrictive measures. Populations that are vulnerable to this outbreak and its physical and mental health effects include community-dwelling older adults with mild cognitive impairment or mild dementia. Telehealth is a potential tool to deliver health care and decrease exposure risk. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…This finding suggests that the means of communication used by elderly individuals to receive information concerning COVID-19 may not provide sufficient or accurate enough information to meet their needs during this period of social isolation. Television was found to be the most used information medium for the elderly participants in this study, which was similar to the findings of a study by Goodman-Casanova [13] that showed television was a major means of providing health information and social support.…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that the means of communication used by elderly individuals to receive information concerning COVID-19 may not provide sufficient or accurate enough information to meet their needs during this period of social isolation. Television was found to be the most used information medium for the elderly participants in this study, which was similar to the findings of a study by Goodman-Casanova [13] that showed television was a major means of providing health information and social support.…”
Section: Discussionsupporting
confidence: 90%
“…Television was found to be the most used information medium for the elderly participants in this study, which was similar to the ndings of a study by Goodman-Casanova [23] that showed television was a major means of providing health information and social support.…”
Section: Discussionsupporting
confidence: 89%
“…Telepsychiatry is becoming a useful tool for patients with mental disorders ( 22 ). For example, a current report on older adults with mild cognitive impairment or mild dementia performed by Telehealth home support shows that those who were living alone during the confinement reported decreased well-being, greater anxiety, and more sleeping problems ( 23 ). Coping with stress and negative and sad emotions have a stronger impact on the elderly due to their age-related immunosenescence and the neuro-immune dysregulation associated with these psycho-social processes ( 24 ).…”
Section: Introductionmentioning
confidence: 99%